Ethnobotanical Surveys of Plants Used by Quilombola Communities in Brazil: A Scoping Review - Letícia Francine Silva Ramos; Ananda Gomes de Sousa; Rebeca de Siqueira Amorim; Alan de Araújo Roque; Israel Luís Diniz Carvalho; Ana Laura Vilela de Carvalho; Milena Evangelista dos Santos; Maiara Bernardes Marques; Luiza Rayanna Amorim de Lima; Moan Jéfter Fernandes Costa; Pedro Henrique Sette-de-Souza (Life, 2024)
Quilombola communities play a crucial role in maintaining biodiversity through traditional management models. The use of medicinal plants within these communities reflects a deep reservoir of knowledge, passed down through generations. The objective of this study was to conduct a scoping review to systematically analyze and synthesize the existing literature on the medicinal plants used by Quilombola communities in Brazil, with a focus on their therapeutic applications and cultural significance. The Population, Concept, and Context (PCC) strategy was utilized, where the population refers to the Quilombolas, the concept pertains to medicinal plants, and the context involves illness. A total of 888 studies were initially identified, but only 10 met the inclusion criteria, covering 297 plant species from 80 different families. These plants are employed in a wide range of therapeutic applications, with decoction, alcohol maceration, and infusion being the most common methods of preparation. The study highlights the rich ethnopharmacological knowledge held by Quilombola communities and underscores the need for greater recognition and integration of this traditional knowledge into public health practices. The conclusion emphasizes the importance of preserving and validating the use of medicinal plants by these communities, which could serve as a foundation for future pharmacological discoveries and the development of culturally appropriate health interventions.